2014
DOI: 10.1007/s11738-014-1569-x
|View full text |Cite
|
Sign up to set email alerts
|

NAC transcription factor expression, amino acid concentration and growth of elite rice cultivars upon salt stress

Abstract: NAC transcription factors (TF) play important roles in regulating osmotic stress tolerance in plants. We tested the expression of 57 NAC genes in the presence of NaCl in young leaves of two elite rice cultivars, Cotaxtla and Tres Ríos, which display contrasting responses to salinity at the biochemical and physiological levels. Using qRT-PCR, the expression of 41 out of 57 NAC genes was validated, of which 23 showed regulation by NaCl. We identified two NAC genes (Os02g56600 and Os12g07790) induced in Cotaxtla,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Primers pairs used in this study were those previously reported by García-Morales et al ( 2014 ) and Caldana et al ( 2007 ). We also tested the expression of the following NAC genes: OsNAC6 (Nakashima et al, 2007 ), OsNAC5 (Sperotto et al, 2009 ), and OsNAC10 (Jeong et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primers pairs used in this study were those previously reported by García-Morales et al ( 2014 ) and Caldana et al ( 2007 ). We also tested the expression of the following NAC genes: OsNAC6 (Nakashima et al, 2007 ), OsNAC5 (Sperotto et al, 2009 ), and OsNAC10 (Jeong et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…These cultivars were produced for establishment in the tropical soils of Mexico, which display different degrees of acidity. The seeds of these cultivars were disinfected and germinated according to García-Morales et al (2014) [43]. Eleven days after germination, plants were transplanted in containers with 12 L Yoshida nutrient solution which contained 1.43 mM NH 4 NO 3 , 1.00 mM CaCl 2 2H 2 O, 1.64 mM MgSO 4 7H 2 O, 1.30 mM K 2 SO 4 , 0.32 mM NaH 2 PO 4 2H 2 O, 1.00 mM Fe-EDTA, 7.99 μM MnCl 2 4H 2 O, 0.15 μM ZnSO 4 7H 2 O, 0.15 μM CuSO 4 5H 2 O, 0.075 μM (NH 4 ) 6 Mo 7 O 24 4H 2 O, and 1.39 μM H 3 BO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Three independent biological replicates were immediately frozen in liquid nitrogen and stored at -80 ºC. RNA extraction, cDNA synthesis, and qRT-PCR were carried out as described by García-Morales et al (2014) [43] and Moreno-Alvarado et al (2017) [1]. The primers for the NAC transcription factors were those previously used by García-Morales et al (2014) [43] and selected from those reported by Caldana et al (2007) [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the biotic stress responsive gene models to (PaNAC03, PaNAC04, PaNAC05 and MA_86256p0010) cluster together in the phylogeny with MA_103386p0010 and MA_64687p0010, which do not respond to H. annosum s.l. inoculation, forming a sister group to the Arabidopsis ANAC032, ATAF1, ATAF2 and ANAC102 proteins and to a group of rice NAC genes known to respond to abiotic stress [58]. This differentiation in terms of expression pattern between Norway spruce paralogs is consistent with the concept of subfunctionalization [59].…”
Section: Discussionmentioning
confidence: 65%